Perancangan Sistem Pelayanan Administrasi Kependudukan dalam Menunjang Digitalisasi Desa - Maulana, Riky Rinaldy; Priatna, Ramdani (STMIK Budi Darma, 2021)
Implementation of Village Digitization is a program that is currently being pushed by the central government to advance village governments in developing governance and services provided to the community, this also encourages Pagerwangi Village in West Bandung Regency to be able to carry out village digitization. The program implemented by the Pagerwangi Village Government is a village administration service system in collaboration with the Village Development Study Center which aims to make it easier for the community to receive services provided by the village government, one form of the village administration service system designed by the Pagerwangi village government. related to correspondence needed by the community in the hope of being more affective and efficient than the previous service. The village administration service system is currently still in the drafting process because there are still some shortcomings and obstacles faced so that it takes time to be applied to the community